Low Risk of Coronavirus Disease 2019 (COVID-19) Among Patients Exposed to Infected Healthcare Workers. (28th August 2020) - Baker, Meghan A; Fiumara, Karen; Rhee, Chanu; Williams, Sarah A; Tucker, Robert; Wickner, Paige; Resnick, Andrew; Klompas, Michael
Abstract: Many patients are fearful of acquiring coronavirus disease 2019 (COVID-19) in hospitals and clinics. We characterized the risk of COVID-19 among 226 patients exposed to healthcare workers with confirmed COVID-19. One patient may have been infected, suggesting that the risk of COVID-19 transmission from healthcare workers to patients is generally low.